Preliminary archaeological findings from recent excavations of a Sarmatian (Iron Age) kurgan site at Karaoba, Kostanay Region, Kazakhstan. (December 2022) - Onggaruly, Akhan; Coil, Reed; Pugh, Christina; Tashmanbetova, Zhuldyz; Kairmagambetov, Arhat; Davlatova, Tamarakhonum; Makulbekova, Madina
Abstract: This paper presents Karaoba, a 4th-2nd centuries BCE Sarmatian burial complex in the Kostanay Region of northwestern Kazakhstan, which exists on the very eastern margins of Sarmatian cultural influence. The undercut burial style is common in the southern Urals and western Kazakhstan, but rare in this region; Karaoba is one of the few examples of its presence this far east. Preliminary findings from the burial within Kurgan № 3 suggest that the individual was a male member of tribal nobility as interpreted through associated ceramic styles, gold objects, and a semi-complete horse skeleton. In all, Karaoba represents one of the most eastern expansions of Sarmatian cultural influence which offers new insights into their geographic range and subsequent cultural expansions.